2019
DOI: 10.15360/1813-9779-2019-6-50-61
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Fluorescence Spectroscopy in the Diagnosis of Tissue Hypoxia (Review)

Abstract: The aim of review is to discuss the results of studies on diagnosis of tissue hypoxia by laser-induced spectroscopy, as well as to identify promising trends and prospects of this technique for its further application in experimental and clinical medicine.The review presents the findings of studies of the fluorescence intensity of endogenous fluorophore molecules (reduced nicotinamide adenine dinucleotide, oxidized flavin adenine dinucleotide) as markers of ischemic injury of internal organs (brain, heart, live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…It was found that this phenomenon is associated mainly with endogenous porphyrins [5]. Much more biochemical substances are emitted (luminescent) in the blue and yellow-green regions of the spectrum: reduced pyridine nucleotides (NAD-H, NADF-H), oxidized flavoproteins (FMN, FAD), vitamins, metabolic products, including pyridoxal, folic acid, its derivatives, etc [5,10].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It was found that this phenomenon is associated mainly with endogenous porphyrins [5]. Much more biochemical substances are emitted (luminescent) in the blue and yellow-green regions of the spectrum: reduced pyridine nucleotides (NAD-H, NADF-H), oxidized flavoproteins (FMN, FAD), vitamins, metabolic products, including pyridoxal, folic acid, its derivatives, etc [5,10].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been conducted on the use of AF-based methods to distinguish pathological from physiological conditions in cells and tissues. A large number of methods for studying typical pathological processes based on the obtained results of AF analysis have been proposed [6][7][8][9][10][15][16][17][18][19][20][21][22][23][24][25][26]. However, despite the accumulated extensive experimental experience, this method has not yet become widespread in medical diagnostic practice, as it is necessary to address the issue of standardization of research methods.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations